Importance of long-range interactions in chemical reactions at cold and ultracold temperatures - Weck, Philippe F.; Balakrishnan, N. (International reviews in physical chemistry, 2006)
We review the recent progress achieved in the theoretical description of chemical reactions at low temperatures. In particular, we discuss the crucial role played by the van der Waals interaction potential in quantum-mechanical scattering calculations of atom-diatom collisions in the cold and ultracold regimes, where abstraction reactions proceed by tunnelling. The importance of zero-energy resonances in enhancing the reactivity in the zero-temperature limit is assessed. The impact of Feshbach resonances associated with the decay of metastable states of van der Waals complexes on reactive scattering is addressed through a series of examples. Finally, we discuss the sensitivity of the reaction dynamics to the topology of the van der Waals well.